Pengaruh Diferensiasi Produk Terhadap Minat Beli Konsumen (Studi Kasus Banana Pop Kota Bima) - Dessy Sahur Ramdini; Ismunandar Ismunandar (Universitas Batanghari, 2020)
Consumers As A Target Market Have Sufficient Preferences Regarding The Products They Buy. These Products Must Be Unique So That Competitors Are Difficult To Imitate. Therefore The Purpose Of This Study Is To Determine Whether There Is An Influence And Positive And Significant Difference Between Product differentiation On Consumer Purchase Interest In Banana Pop City Of Bima. The Research Method Used In This Study Is The Associative Method. The Technique Of Determining The Sample Uses The Unknown Population With The Formula: Number Of Samples = Number Of Indicators 10 = 10 X 10 = 100, With A Sample Size Of 100 Respondents. Data Collection Techniques Are Observation, Questionnaire / Questionnaire, Literature Study. Data Analysis Techniques Using Simple Linear Regression Analysis, Simple Correlation Coefficient, Coefficient Of Determination, T Test With Spss 20 For Windows. The Results Of The Study Stated That The Validity And Reliability Tests Stated Validity And Reliability For All Data. In The Test Significant Test (T Test) States With The Value Ttable > Tcount (1.984 > -1819) And Sig Value 0.072> 0.05, So It Falls On The Rejection Ha Region Which Means H0 Is Rejected, Then It Can Be Interpreted That There Is No Influence Positive And Significant Between Product Differentiation Against Consumer Buying Interest In Banana Pop City Of Bima.